Pembrolizumab as an immunotherapy drug in the treatment of a patient with recurrent (unresectable) cancer of the lower lip - Markulan, L. Y.; Makarevych, L. M. (General Surgery, 2022)
Advances in immunotherapy have changed approaches to the treatment of recurrent and/or metastatic head and neck squamous cell carcinoma (R/M HNSCC). The US Food and Drug Administration (the FDA) has approved both pembrolizumab monotherapy for first‑line treatment of the tumours expressing the programmed cell death receptor‑1 (PD‑L1; combined positive score of ≥ 1) in patients with R/M HNSCC and pembrolizumab administration in combination with platinum and fluorouracil regardless of the level of PD‑L1 expression. Pembrolizumab is a humanized monoclonal antibody class drug that activates the anti‑tumour immune response. Objective — to present treatment outcomes for recurrent (unresectable) cancer of the lower lip that was treated using a pembrolizumab monotherapy regimen. Patient H., born in 1968, received a 20‑month combined therapy for cancer of the lower lip. He had radical surgical removal of the primary tumour and two surgical resections of metastases, as well as courses of both remote gamma‑therapy and polychemotherapy. Nevertheless, the disease progressed from T2N0M0 to T4N1M0. In the area of the chin and right cheek, the patient developed a defect of the skin and subcutaneous tissue measuring 18 ´ 10 cm with purulent‑necrotic margins and an external fistula of the oral cavity. He was also bothered by unbearable pain in the area of the tumour and an unpleasant odour from the mouth and from the tumour. The patient was prescribed immunotherapy with pembrolizumab since an immunohistochemical examination revealed an RD‑L1‑positive tumour. One year after the start of immunotherapy, which included 17 courses of cancer treatment, the wound healed and the patient’s quality of life significantly improved. No adverse reactions were observed during immunotherapy. Computed tomography revealed a 25 x 15 mm nodule at the level of the lower jaw on the right and a lymph node of about 10 mm in diameter in the area of the lower parts of the right parotid salivary gland. Distant metastases were not detected. Currently, immunotherapy is ongoing. The issue of surgical removal of pathological formations is under consideration. This case demonstrates the positive outcomes of a pembrolizumab monotherapy regimen in a patient with R/M HNSCC.